2019
DOI: 10.1097/md.0000000000014022
|View full text |Cite
|
Sign up to set email alerts
|

Maximum standardized uptake value of foot SPECT/CT using Tc-99m HDP in patients with accessory navicular bone as a predictor of surgical treatment

Abstract: Quantitative bone SPECT/CT (single-photon emission computed tomography/computed tomography) using Tc-99m hydroxymethylene diphosphonate is emerging as a useful imaging modality for skeletal diseases. Accessory navicular bone (ANB) has been evaluated by bone scintigraphy only qualitatively and semiquantitatively. However, a truly objective quantitative assessment of ANB is lacking. Here, we measured the maximum standardized uptake value (SUVmax) of the ANB and investigated its usefulness as an imaging biomarker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…Symptomatic ANB often shows increased bone tracer uptake [16,17] but a thorough investigation regarding the role of bone SPECT/CT has never been conducted probably because of lack of objective methods for the assessment of bone tracer uptake [18,19]. We calculated the SUV max over the ANB and correlated it with clinical outcomes [20]. As expected, higher SUV max was correlated with aggressive type of ANB.…”
Section: Bone or Joint Diseasementioning
confidence: 96%
“…Symptomatic ANB often shows increased bone tracer uptake [16,17] but a thorough investigation regarding the role of bone SPECT/CT has never been conducted probably because of lack of objective methods for the assessment of bone tracer uptake [18,19]. We calculated the SUV max over the ANB and correlated it with clinical outcomes [20]. As expected, higher SUV max was correlated with aggressive type of ANB.…”
Section: Bone or Joint Diseasementioning
confidence: 96%
“…An accessory navicular bone is usually bilateral. 1 Bae et al 1 reported a study including 74 patients with ANB with 7 unilateral and 67 bilateral in their series. The strength of our study was including 41 patients with unilateral ANB.…”
Section: Discussionmentioning
confidence: 99%
“…Recently,with the introduction of CT-based attenuation correction,the error of calculating SUV in SPECT/CT images was less than 10% [15],leading to the widespread use of SPECT/CT bone quantification in clinical studies. SPECT/CT quantification has been demonstrated as an efficient tool for evaluating the efficacy of disease [16] [17] and identifying the benign and malignant bone diseases [18].To the best of our knowledge, this is the first large sample study to obtain SUV measurements of all 24 vertebrae based on OSCG-enhanced reconstruction algorithm of CT attenuation correction.…”
Section: Discussionmentioning
confidence: 99%